1989
DOI: 10.1093/jn/119.11.1610
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Raw Potato Starch Alters Intestinal Function and Colonic Cell Proliferation in the Rat

Abstract: Raw potato starch (RPS) may escape complete digestion to enter the colon and produce alterations in colonic function, while cooked potato starch (CPS) is nearly completely digested in the rat small intestine. Effects of RPS and CPS on colonic function [fecal weight, transmit time and thymidine kinase (TK) activity (a marker for cell proliferation)] were contrasted in a 6-wk feeding study. Male F344 rats consumed either dextrose/sucrose (DS; control), 30% CPS or 30% RPS diet. RPS feeding resulted in a 3-fold in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 27 publications
5
18
0
Order By: Relevance
“…This high content of starch evoked a significant, although not high, increase in the mass of the Table 3 Bacterial glycolytic activity in the caecal digesta (U/g fresh content or U/g À2 protein a ) of the rats The values within column with different letters (a, b) are significantly different at P < 0.05. caecum wall of rats, compared to the control group (Table 2). It was consistent with the results of other authors (Calvert, Otsuda, & Satchihanandam, 1989;Mathers, Smith, & Carter, 1997), who reported on the hypertrophy of the caecum after consuming diet with potato starch. It is probably an adaptive response to enable salvage of energy from fermentation of starch escaping small-bowel digestion (Mathers & Dawson, 1991).…”
Section: Discussionsupporting
confidence: 93%
“…This high content of starch evoked a significant, although not high, increase in the mass of the Table 3 Bacterial glycolytic activity in the caecal digesta (U/g fresh content or U/g À2 protein a ) of the rats The values within column with different letters (a, b) are significantly different at P < 0.05. caecum wall of rats, compared to the control group (Table 2). It was consistent with the results of other authors (Calvert, Otsuda, & Satchihanandam, 1989;Mathers, Smith, & Carter, 1997), who reported on the hypertrophy of the caecum after consuming diet with potato starch. It is probably an adaptive response to enable salvage of energy from fermentation of starch escaping small-bowel digestion (Mathers & Dawson, 1991).…”
Section: Discussionsupporting
confidence: 93%
“…Resistant starch is utilized by intestinal microflora (6) and seems to affect the cecal and colonic functions (7). It is contained in rice starch and potato starch, but little information is available about the influence of the source of starch in the diet on the metabolism of dietary isoflavones.…”
Section: Discussionmentioning
confidence: 99%
“…The four intestinal segments stretched on filter paper were prefixed with Bouin's fluid containing 2.5% glacial acid for 90 to 120 min at room temperature. The prefixed segments were then rolled into a spiral with the mucosa facing inward, so as to form a "Swiss roll" similar to that described by Calvert et al (1989) with adaptations. The rolls were tied with string and fixed in Bouin's for an additional 18 to 20 h (Fig.…”
Section: Methodsmentioning
confidence: 99%